'Mr Haughey's silence condemns him': Charles J. Haughey and the second Republican hunger strike, 1981. Issue 3 (3rd July 2017) - Kelly, Stephen
ABSTRACT: This article examines Charles J. Haughey's involvement with the second Republican hunger strike, which lasted from March to October 1981. For the first time it reveals the true extent of how Haughey, Fianna Fáil leader and taoiseach during the depths of this crisis, was forced to play a marginal role, banished to the political side-lines. His repeated attempts to act as a mediator between British prime minister Margaret Thatcher and the Republican movement, in an effort to bring the hunger strike to an amicable conclusion, was an abject failure.